Water quality of the Grijalva river in the Chiapas and Tabasco border - Musalem-Castillejos, Karim; Laino-Guanes, Rafael; Bello-Mendoza, Ricardo; González-Espinoza, Mario; Ramírez-Marcial, Neptalí (Ecosistemas y Recursos Agropecuarios, 2018)
The objective was to characterize water quality for a section of the Grijalva River and its tributaries, for rainy and dry season in the border of the States of Chiapas and Tabasco. 23 physical, chemical, and microbiological parameters as well as contaminants were determined and compared with the Mexican norm NOM-127-SSA1-1994 which establishes water quality maximum permissible limits for use and human consumption and with the water quality classi cation scale proposed by the Comisión Nacional del Agua. Water quality of the Grijalva River in the studied section and tributaries, also locally named Almandros river, decreases as it descends to more populated areas of Tabasco. Water turbidity and high levels of coliforms and Escherichia are the main problems associated with the rivers of the studied area, even in water sources destined for human consumption. Other studied parameters have acceptable water quality mainly during the dry season, except for Mercury, which showed higher levels than the recommended by the norm in all sampling sites. The need to further study presence of Mercury in the Grijalva River basin is suggested.